The interrelatedness between the content-based approach and EFL University students’ emotional intelligence - Ismaeel, Ansam Ali; Saleh Khaleif, Khalil (Opción, 2019)
This study aims at examining the relationship between emotional intelligence and the variable of academic achievement on the one hand, and the role of the content-based approach in achieving this relation on the other hand. To bring about such kind of interrelation, a design of a pre-post-test has been used. The main findings of the study show that there is a positive relationship between participants’ emotional intelligence skills. In conclusion, the use of the content-based approach in teaching students enhances the effect of emotional intelligence on their academic achievement.